2021
DOI: 10.1101/2021.08.26.457296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allele expression biases in mixed-ploid sugarcane accessions

Abstract: Allele-specific expression (ASE) represents differences in the magnitude of expression between alleles of the same gene. This is not straightforward for polyploids, especially autopolyploids, as knowledge about the dose of each allele is required for accurate estimation of ASE. This is the case for the genomically complex Saccharum species, characterized by high levels of ploidy and aneuploidy. We used a Beta-Binomial model to test for allelic imbalance in Saccharum, with adaptations for mixed-ploid organisms.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…A Bayesian hierarchical beta-binomial model ( Correr et al 2021 ) confirmed that most SNVs showed no evidence of ASE, with 19,154 to 56,956 heterozygous sites yielding significant tests ( Table 1 ; Supplemental Fig. S6 ).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…A Bayesian hierarchical beta-binomial model ( Correr et al 2021 ) confirmed that most SNVs showed no evidence of ASE, with 19,154 to 56,956 heterozygous sites yielding significant tests ( Table 1 ; Supplemental Fig. S6 ).…”
Section: Resultsmentioning
confidence: 86%
“…Different statistical models and testing strategies, hard thresholds, and other ad hoc criteria can affect the results. In sugarcane, Correr et al (2021) also observed ASE for ∼40% of the sampled genes. However, this study relied on genotyping-by-sequencing of reduced representation libraries, a strategy that is prone to biases and genotyping errors ( Scheben et al 2017 ).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations